2017
DOI: 10.5312/wjo.v8.i6.465
|View full text |Cite
|
Sign up to set email alerts
|

Emergent reintubation following elective cervical surgery: A case series

Abstract: AIMTo review cases of emergent reintubation after cervical surgery.METHODSPatients who were emergently intubated in the post-operative period following cervical surgery were identified. The patients’ prospectively documented demographic parameters, medical history and clinical symptoms were ascertained. Pre-operative radiographs were examined for the extent of their pathology. The details of the operative procedure were discerned.RESULTSEight hundred and eighty patients received anterior- or combined anterior-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Wewel et al reported that, out of seventy-two patients who underwent PAP and AP surgeries, six had delayed extubation, and three had reintubation [ 32 ]. The reintubation of 9 patients out of 880 that underwent elective cervical surgery, 3 of whom underwent combined anterior–posterior surgery, was also reported by Schroeder et al [ 33 ]. In all of these accounts, the combined anterior–posterior surgery procedure was performed in a single stage.…”
Section: Discussionsupporting
confidence: 60%
“…Wewel et al reported that, out of seventy-two patients who underwent PAP and AP surgeries, six had delayed extubation, and three had reintubation [ 32 ]. The reintubation of 9 patients out of 880 that underwent elective cervical surgery, 3 of whom underwent combined anterior–posterior surgery, was also reported by Schroeder et al [ 33 ]. In all of these accounts, the combined anterior–posterior surgery procedure was performed in a single stage.…”
Section: Discussionsupporting
confidence: 60%
“…Schroeder et al concluded that if a secure airway is restored quickly, the patients’ outcomes are mostly favorable. 18 Prior to extubation, the medical team should have an airway management plan in place in the event airway compromise occurs and reintubation is necessary. This plan should include having advanced airway devices immediately available, staff trained to identify at risk patients, and access to a surgeon capable of performing a surgical airway.…”
Section: Resultsmentioning
confidence: 99%
“…Airway obstruction following postoperative extubation following anterior cervical spine surgery represents a much-dreaded complication. It has many potential causes and is particularly concerning to surgeons because of its potential to quickly progress to respiratory arrest and death complicating a procedure that most of the time is considered “straightforward.” Airway complication rates are quoted around 1% of all anterior cervical procedures, usually restricted to 1- or 2-level pathology and are frequently discussed in the literature in the context of outpatient anterior cervical surgery and its safety [ 18 , 19 ]. This has led authors to identify patients at-risk for unplanned reintubation.…”
Section: Discussionmentioning
confidence: 99%